Multiring techniques for scalable battlespace group communications. - Wang, Jun.
Network-centric warfare must leverage off a common network to support different purposes. While group communications based on a single virtual ring overlay may satisfy the most important requirements for survivability and security, scalability may for cc redesign because a single ring generally has higher delay and delay jitter. In order to provide scalability as the number of group members grows, large single rings may be broken into, smaller multirings interconnected together. Thus, comparing the characteristics of different multiring techniques provides insight into which battlespace applications may be supported via virtual rings. In this article we consider different approaches to providing scalable battlespace group communications using multi-ring techniques, classifying the techniques according to the primary military requirements of QoS, security, and survivability. Some important design issues of multiring techniques, such as the number of ring levels and number of rings per level, are dependent on, application QoS requirements and the underlying network infrastructure in terms of topology (dense vs. sparse) and link bandwidths (bottleneck capacities). Through our survey, we conclude that while no existing multiring scheme provides the single solution to battlespace group communications, some aspects of existing multiring schemes do match specific scenarios and provide us useful insights for designing new schemes for battlespace group communication. To our knowledge, this is the first article to survey and categorize multiring algorithms.
Keywords: QoS; communications scalability; link bandwidths; multiring techniques; network-centric warfare; scalable battlespace group communications; topology bandwidths